Unravelling the Enigma: A Study on Exploring the Idiopathic Surge in Serum Alkaline Phosphatase Level - KR, Vishal (International Journal of Medicine, 2024)
A 73 year old Indian female with type O blood group came for routine checkup when it was discovered she had elevated levels of serum alkaline phosphatase (600 mg/dL). Other liver function tests were within normal limits. Abdominal imaging revealed grade I fatty liver but an extensive serological search for significant hepatobiliary disease was negative. She is currently under medication for diabetes and hypertension, association with raised enzyme level couldn't be interpreted due to paucity of testing.